Prototype of a Peak to Average Power Ratio Reduction Scheme in Orthogonal Frequency Division Multiplexing Systems - Varahram, P.; Ali, B.M.; Mohammady, S.; Reza, A.W. (Korean Society for Internet Information, 2015)
Peak to average power ratio (PAPR) is one of the main imperfections in the broadband communication systems with multiple carriers. In this paper, a new crest factor reduction (CFR) scheme based on interleaved phase sequence called Dummy Sequence Insertion Enhanced Partial Transmit Sequence (DSI-EPTS) is proposed which effectively reduces the PAPR while at the same time keeps the total complexity low. Moreover, the prototype of the proposed scheme in field programmable gate array (FPGA) is demonstrated. In DSI-EPTS scheme, a new matrix of phase sequence is defined which leads to a significant reduction in hardware complexity due to its less searching operation to extract the optimum phase sequence. The obtained results show comparable performance with slight difference due to the FPGA constraints. The results show 5 dB reduction in PAPR by applying the DSI-EPTS scheme with low complexity and low power consumption.